An African Biblical Interpretation of Matthew 20:1-15 in relation to social justice for workers in Cameroon - van Eck, Ernest; Ntem, Godlove S (Stellenbosch Theological Journal, 2021)
After the colonial era in the early sixties, the practice of employing and paying workers in Cameroon both in the civil service and in the private sector became very crucial, considering the fact that the situation of unemployment is so endemic to Cameroon as a paradigm for Africa's unemployment. From an economic perspective, Cameroon has a booming labour force, but this robust manpower has been underutilized due to the provocative unemployment that is experienced in all sectors in the country. As an agrarian economy, the weakness of industrialization in Cameroon does not offer mass employment alternatives. Those who have the privilege to be employed are not satisfied with their remunerations to the extent that they try to use unorthodox means to add to their pay through corruption. This article highlights the desperate nature of Cameroonian workers through the lenses of Matthew 20:1-15. It is a society of unfair distribution of resources and this creates an imbalanced society between the privileged and non-privileged peasantry.